(untitled) (Journal of Laboratory Animal Science, 2019)
Animal models are well documented in the literature and are used for experimentation due to their specific characters or response to the chemicals. Any deviation of these animals from the reported characters or response renders the animal unsuitable for the research. Therefore, use of genetically defined laboratory animal model is equally important to that of use of pure chemicals in any biomedical research. Procurement of pure lines and their sustained maintenance in the animal facility is of utmost importance for the existence and functioning of any animal facility. Keeping in view of the fact that despite careful and defined breeding program, genetic contamination and strain alterations may occur. The present study was undertaken to ascertain the genetic purity of strains of laboratory mice maintained at ACTREC. Skin grafting, coat colour testing and seven biochemical markers were studied. The results of all these tests showed that the rodent strains maintained at ACTREC have no genetic contaminations/ drift even after maintaining the strains for as many as 136 generations. The data indicates that merely conducting these simple tests, it is possible to establish in-house genetic quality control program and check the authenticity of the laboratory animals.